A new attempt at the estimation for the noise level probability distribution based on specific L_x noise evaluation indices - OHTA, M.; MITANI, Y. (Archives of Acoustics, 1990)
In this paper, a new attempt at the estimation for the noise level probability distribution is proposed based on the known values of several specific L_x noise evaluation indices. Here, the effect of the restricted amplitude fluctuation range matched to the actual stochastic phenomenon on the estimation accuracy is reasonably taken into consideration. The effectiveness of the proposed method is experimentally confirmed by applying it to theactually measured road traffic noise data.